Investigation of white standards by means of bidirectional reflection distribution function and integrating sphere methods - Jaglarz, Janusz; Duraj, Ryszard; Szopa, Przemysław; Cisowski, Jan; Czternastek, Halina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The paper deals with investigation of the white Lambertian standards by means of optical methods, i.e., the bidirectional reflection distribution function (BRDF) method and the reflectance study with an integrating sphere. All measurements have been made using the L*a*b* color system. The effect of the choice of a standard on values of trichromatic parameters and the effect of aging of standards is discussed.
Optica Applicata, Vol. 36, 2006, nr 1, s. 97-103
Keywords: optyka; optical scattering; white standards; color measurements